Establishment of a Novel Humanized Mouse Model To Investigate In Vivo Activation and Depletion of Patient-Derived HIV Latent Reservoirs - Flerin, Nina C. (J Virol, 2019)
Curing HIV infection has been thwarted by the persistent reservoir of latently infected CD4(+) T cells, which reinitiate systemic infection after antiretroviral therapy (ART) interruption. To evaluate reservoir depletion strategies, we developed a novel preclinical in vivo model consisting of immunodeficient mice intrasplenically injected with peripheral blood mononuclear cells (PBMC) from long-term ART-suppressed HIV-infected donors. In the absence of ART, these mice developed rebound viremia which, 2 weeks after PBMC injection, was 1,000-fold higher (mean = 9,229,281 HIV copies/ml) in mice injected intrasplenically than in mice injected intraperitoneally (mean = 6,838 HIV copies/ml) or intravenously (mean = 591 HIV copies/ml). One week after intrasplenic PBMC injection, in situ hybridization of the spleen demonstrated extensive disseminated HIV infection, likely initiated from in vivo-reactivated primary latently infected cells. The time to viremia was delayed significantly by treatment with a broadly neutralizing antibody, 10-1074, compared to treatment with 10-1074-FcR(null), suggesting that 10-1074 mobilized Fc-mediated effector mechanisms to deplete the replication-competent reservoir. This was supported by phylogenetic analysis of Env sequences from viral-outgrowth cultures and untreated, 10-1074-treated, or 10-1074-FcR(null)-treated mice. The predominant sequence cluster detected in viral-outgrowth cultures and untreated mouse plasma was significantly reduced in the plasma of 10-1074-treated mice, whereas two new clusters emerged that were not detected in viral-outgrowth cultures or plasma from untreated mice. These new clusters lacked mutations associated with 10-1074 resistance. Taken together, these data indicated that 10-1074 treatment depletes the reservoir of latently infected cells harboring replication competent HIV. Furthermore, this mouse model represents a new in vivo approach for the preclinical evaluation of new HIV cure strategies. IMPORTANCE Sustained remission of HIV infection is prevented by a persistent reservoir of latently infected cells capable of reinitiating systemic infection and viremia. To evaluate strategies to reactivate and deplete this reservoir, we developed and characterized a new humanized mouse model consisting of highly immunodeficient mice intrasplenically injected with peripheral blood mononuclear cells from long-term ART-suppressed HIV-infected donors. Reactivation and dissemination of HIV infection was visualized in the mouse spleens in parallel with the onset of viremia. The applicability of this model for evaluating reservoir depletion treatments was demonstrated by establishing, through delayed time to viremia and phylogenetic analysis of plasma virus, that treatment of these humanized mice with a broadly neutralizing antibody, 10-1074, depleted the patient-derived population of latently infected cells. This mouse model represents a new in vivo approach for the preclinical evaluation of new HIV cure strategies.